Counseling Guidance Services in Improving Learning Motivation Post Covid 19 - Fadila Fadila; Sovatunisa Soleha; Febriansyah Febriansyah; Beni Azwar (STAI Hubbulwathan Duri, 2022)
After going through the online teaching and learning process which was carried out at SMP Negeri L. Sidoharjo, students got used to studying at home and playing on cell phones until they forgot the teaching and learning process had been done face-to-face, so some children had problems studying at school, including not doing assignments school, lazy to study, often play online games, and skip school. Even from observations, some students received a summons, and their parents were called for not attending school without permission and not doing schoolwork. This study aims to determine the teaching and learning process after doing the online learning process, the effect of online learning on students' learning motivation, and the efforts of the supervising teacher in increasing student learning motivation. This type of research is descriptive and qualitative. Sources of data come from primary data and secondary data, the subjects in this study were the supervising teacher, homeroom teacher, and class VIII students. Techniques used in data collection by observation, interviews, and documentation. The data analysis technique uses data reduction, data presentation, and concluding. The results showed that the online teaching and learning process affects students' learning motivation which causes students' learning motivation to decrease, as can be seen from the attitudes, values , and behavior of students during the teaching and learning process. The efforts of the supervising teacher in increasing the learning motivation of class VIII students of SMP Negeri L. Sidoharjo using information services and individual counseling and taking an emotional approach to explore various information, provide encouragement, guidance, and direction, provide examples, and work together with homeroom teachers, teachers subjects for home visits, it is hoped that parents know and can contribute to helping increase student learning motivation. Obstacles faced by supervising teachers to increase student learning motivation are the lack of enthusiasm from within students, lack of attention to direction and guidance from teachers, and lack of support from the environment such as parents and students' peers.After going through the online teaching and learning process which was carried out at SMP Negeri L. Sidoharjo, students got used to studying at home and playing on cell phones until they forgot the teaching and learning process had been done face-to-face, so some children had problems studying at school, including not doing assignments school, lazy to study, often play online games, and skip school. Even from observations, some students received a summons, and their parents were called for not attending school without permission and not doing schoolwork. This study aims to determine the teaching and learning process after doing the online learning process, the effect of online learning on students' learning motivation, and the efforts of the supervising teacher in increasing student learning motivation. This type of research is descriptive and qualitative. Sources of data come from primary data and secondary data, the subjects in this study were the supervising teacher, homeroom teacher, and class VIII students. Techniques used in data collection by observation, interviews, and documentation. The data analysis technique uses data reduction, data presentation, and concluding. The results showed that the online teaching and learning process affects students' learning motivation which causes students' learning motivation to decrease, as can be seen from the attitudes, values , and behavior of students during the teaching and learning process. The efforts of the supervising teacher in increasing the learning motivation of class VIII students of SMP Negeri L. Sidoharjo using information services and individual counseling and taking an emotional approach to explore various information, provide encouragement, guidance, and direction, provide examples, and work together with homeroom teachers, teachers subjects for home visits, it is hoped that parents know and can contribute to helping increase student learning motivation. Obstacles faced by supervising teachers to increase student learning motivation are the lack of enthusiasm from within students, lack of attention to direction and guidance from teachers, and lack of support from the environment such as parents and students' peers.